Adhesive composition and protective sheet
By using adhesive compositions of polyurethane, ethylenically unsaturated monomer and photopolymerization initiator in the protective sheet of optical components, the cutting chip and breakage of the adhesive layer of the protective sheet during cutting and peeling is solved, and the problem of cutting chips and breakage of the adhesive layer is achieved. Moderate peeling force and strength are suitable for modern large-screen and thin-film equipment.
Patent Information
- Application Number
- CN202380038779.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-04-26
- Publication Date
- 2024-12-17
AI Technical Summary
The protective sheet of existing optical components is prone to cutting chips and breakage of the adhesive layer during cutting and peeling, and the peeling strength is insufficient, making it difficult to meet the needs of modern large-screen and thin-film equipment.
Adhesive compositions containing polyurethane, ethylenically unsaturated monomers and photopolymerization initiators are used to adjust the structure and component ratio of the polyurethane to increase the strength and peeling force of the adhesive layer, and reduce the generation of cutting chips.
It effectively reduces the generation of cutting chips during cutting and damage to the adhesive layer, provides moderate peeling force and strength, and is suitable for protective sheets of modern optical components.
Smart Images

Figure BDA0005121013480000171 
Figure BDA0005121013480000181 
Figure BDA0005121013480000191
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition and a protective sheet.
[0002] This application claims priority based on Japanese Patent Application No. 2022-110520 filed in Japan on July 8, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] Various optical films are used in optical components such as liquid crystal displays and touch panels of smartphones, personal computers, and televisions. In order to prevent contamination and damage in the conveying process, manufacturing process, and inspection process, a protective sheet (surface protective sheet) is generally laminated on the surface of these optical films. The protective sheet is peeled off in the subsequent process such as the assembly process. As adhesives for such protective sheets, various urethane adhesives have been proposed.
[0004] For example, Patent Document 1 discloses a UV-curable adhesive composition for a protective film comprising polyurethane (A), alkyl mono(meth)acrylate (B) having an alkyl group with 6 to 18 carbon atoms, multifunctional (meth)acrylate (C), and plasticizer (D). The polyurethane (A) is a reaction product of a polyol (a1), a polyisocyanate (a2), a hydroxyl-containing (meth)acrylate (a3), and a hydroxyl-containing photopolymerization initiator (a4).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-164840 Summary of the invention
[0008] Problems to be solved by the invention
[0009] These protective sheets are sometimes cut into a desired shape with a cutter or the like in the process before or after pasting to the adherend. At this time, sometimes the cut-off scraps of the adhesive layer are generated in the cross section of the protective sheet, resulting in contamination of the adherend surface. In addition, when the lamination and peeling operations of the protective sheet are repeatedly performed, or when an impact is applied from the outside, the adhesive layer is sometimes damaged and the adherend is contaminated, or the impact is transmitted to the adherend due to the insufficient strength of the adhesive layer and is damaged. In recent years, with the large screen of the display and the thin film of the panel components, the optical components themselves are prone to cracking. Therefore, it is also required that the protective sheet can be peeled off with a lighter force (light peelability) while having moderate adhesion (peel strength).
[0010] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide an adhesive composition which can reduce generation of cutting scraps during cutting and damage to the adhesive layer and can obtain an adhesive layer having appropriate peeling force and strength.
[0011] Another object of the present invention is to provide a protective sheet having an adhesive layer which reduces generation of cutting scraps during cutting and damage to the adhesive layer and has appropriate peeling force and strength.
[0012] Means for solving problems
[0013] The present invention includes the following aspects.
[0014] [1] An adhesive composition comprising:
[0015] Polyurethane (A),
[0016] a monomer (B) containing an ethylenically unsaturated group, and
[0017] Photopolymerization initiator (C),
[0018] The polyurethane (A) is a polyurethane having a skeleton including a structure derived from a polyol and a structure derived from a polyisocyanate, and having an ethylenically unsaturated group at a terminal.
[0019] The weight average molecular weight of the polyurethane (A) is 3,000 to 30,000.
[0020] [2] The adhesive composition according to [1], wherein the polyol is a polyoxyalkylene polyol having a number average molecular weight of 300 to 1800.
[0021] [3] The adhesive composition according to [1] or [2], wherein the ethylenically unsaturated group equivalent of the polyurethane (A) is 900 to 3000 g / mol.
[0022] [4] The adhesive composition according to any one of [1] to [3], wherein the concentration of the urethane bonds in the polyurethane (A) is 1.0 to 5 mol / kg.
[0023] [5] The adhesive composition according to any one of [1] to [4], wherein the polyurethane (A) has an ethylenically unsaturated group at a site other than a terminal.
[0024] [6] The adhesive composition according to any one of [1] to [5], wherein the polyisocyanate includes a polyisocyanate containing an ethylenically unsaturated group and a polyisocyanate not containing an ethylenically unsaturated group.
[0025] [7] According to any one of [1] to [6], the above-mentioned monomer (B) containing an ethylenically unsaturated group contains a monofunctional (meth)acrylate (B1), and the above-mentioned monofunctional (meth)acrylate (B1) is a chain alkyl (meth)acrylate, and the number of carbon atoms of the chain alkyl is 6 to 18.
[0026] [8] The adhesive composition according to any one of [1] to [7], wherein the ethylenically unsaturated group-containing monomer (B) contains a monofunctional (meth)acrylate (B1) and a polyfunctional (meth)acrylate (B2).
[0027] [9] The adhesive composition according to [8], wherein the composition contains 5 to 89% by mass of a monofunctional (meth)acrylate (B1) and 0.1 to 30% by mass of a polyfunctional (meth)acrylate (B2), relative to 100% by mass of the total of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group.
[0028]
[10] The adhesive composition according to claim 1, wherein the polyurethane (A) is contained in an amount of 10 to 90% by mass, and the monomer (B) containing an ethylenically unsaturated group is contained in an amount of 10 to 90% by mass, relative to 100% by mass of the total of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group.
[0029]
[11] The adhesive composition according to any one of [1] to [9], further comprising a plasticizer (D).
[0030]
[12] The adhesive composition according to
[11] , wherein the adhesive composition contains 0.05 to 5 parts by mass of a photopolymerization initiator (C) and 1 to 30 parts by mass of the plasticizer (D) relative to a total of 100 parts by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group.
[0031]
[13] A cured product of the adhesive composition described in [1] or
[11] .
[0032]
[14] The cured product according to
[13] , wherein the elongation at break is 92 to 300% and the breaking strength is 300 to 800 g / mm 2 .
[0033]
[15] A protective sheet comprising a substrate and an adhesive layer formed on one surface of the substrate and comprising the cured product according to
[13] .
[0034] Effects of the Invention
[0035] According to the present invention, an adhesive composition can be provided that can reduce the generation of cutting scraps during cutting and the damage of the adhesive layer, and has an adhesive layer with appropriate peeling force and strength. In addition, a protective sheet with an adhesive layer that can reduce the generation of cutting scraps during cutting and the damage of the adhesive layer, and has an adhesive layer with appropriate peeling force and strength can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram showing the dimensions of a test piece used in the tensile test of the example.
[0037] Figure 2 This is a microscopic photograph of a cross section of an adhesive sheet obtained in an evaluation test of cutting chips and cracks in an adhesive layer for the protective sheet of Example 1 (using A4300) (upper layer: adhesive layer, lower layer: substrate).
[0038] Figure 3 This is a microscopic photograph of a cross section of an adhesive sheet obtained in an evaluation test of cutting chips and cracks in the adhesive layer for the protective sheet of Comparative Example 1 (using A4300) (upper layer: adhesive layer, lower layer: substrate).
[0039] Figure 4 This is a microscopic photograph of a cross section of an adhesive sheet obtained in an evaluation test of cutting chips and cracks in an adhesive layer for a protective sheet (using A4300) of Comparative Example 4 (upper layer: adhesive layer, lower layer: substrate). DETAILED DESCRIPTION
[0040] The following describes the embodiments of the present invention in detail. However, the present invention is not limited to the embodiments shown below. Here, the so-called (meth)acryloyl group refers to one or more functional groups selected from the group represented by the chemical formula CH2=CH-CO- and the chemical formula CH2=C(CH3)-CO-. The so-called (meth)acryloyloxy group refers to one or more functional groups selected from the group represented by the chemical formula CH2=CH-CO-O- and the chemical formula CH2=C(CH3)-CO-O-.
[0041] <Adhesive composition>
[0042] The adhesive composition of the present embodiment comprises polyurethane (A), an ethylenically unsaturated group-containing monomer (B), and a photopolymerization initiator (C), and may contain a plasticizer (D) as necessary.
[0043] By using the adhesive composition of the present embodiment as the adhesive layer of the protective sheet, the generation of cutting chips during cutting and the damage of the adhesive layer can be reduced. It can be considered that multiple factors are complexly associated with the occurrence of cutting chips and damage of the adhesive layer. For example, various factors including external factors such as the type and thickness of the substrate, the type of adhesive layer, the type and condition of the process when the protective sheet is used, the type of adherend, the type of impact applied from the outside, etc. can be cited. By using a combination of the components used to reduce the factors that are significantly associated with the occurrence of cutting chips and damage of the adhesive layer among these factors, the cutting chips and damage of the adhesive layer can be effectively reduced.
[0044] [Polyurethane (A)]
[0045] The polyurethane (A) used in the present embodiment is a polyurethane having a skeleton including a structure derived from a polyol and a structure derived from a polyisocyanate, and has an ethylenically unsaturated group at the terminal. The so-called "structure derived from a polyol" is a structure introduced by using a polyol as a compound having two or more hydroxyl groups as a raw material of a polyurethane. The so-called "structure derived from a polyisocyanate" is a structure introduced by using a polyisocyanate as a compound having two or more isocyanate groups as a raw material of a polyurethane. As a method for introducing an ethylenically unsaturated group at the terminal, a method of adding an ethylenically unsaturated compound containing a hydroxyl group to a carbamate prepolymer at the terminal of an isocyanate group, and a method of adding an ethylenically unsaturated compound containing an isocyanate group to a carbamate prepolymer at the terminal of a hydroxyl group can be cited. From the viewpoint of reducing the peeling force when the protective sheet is peeled off from the adherend, the polyurethane (A) may also have an ethylenically unsaturated group at a position other than the terminal as required. Examples of a method for introducing an ethylenically unsaturated group into a site other than a terminal include a method of using an ethylenically unsaturated group-containing polyol or an ethylenically unsaturated group-containing polyisocyanate as a raw material for synthesizing the polyurethane (A).
[0046] "Polyols"
[0047] The polyol used in the present embodiment is a compound having no isocyanate group and having two or more hydroxyl groups. From the viewpoint of suppressing gelation during synthesis and making it possible to uniformly extend the polymer, the number of hydroxyl groups possessed by the polyol is preferably two.
[0048] As a preferred polyol, from the viewpoint of increasing the elongation of the adhesive layer and more effectively suppressing the generation of cutting chips during cutting, polyoxyalkylene polyols having a polyoxyalkylene chain can be cited. In particular, when the substrate constituting the protective sheet is hard or thick, when it is cut or subjected to external impact, it is preferred to use polyoxyalkylene polyols as polyols under conditions where cutting chips and breakage are likely to occur due to the brittleness of the adhesive layer. The number of carbon atoms of the alkylene chain constituting the above-mentioned polyoxyalkylene chain is preferably 2 to 8, more preferably 2 to 6, and further preferably 2 to 4. As specific examples, polyoxyethylene polyols, polyoxypropylene polyols, polyoxybutylene polyols, etc. can be cited. In addition, among the polyoxyalkylene polyols, polyoxyalkylene diols are preferably used, polypropylene glycol and polybutylene glycol are particularly preferred, and polypropylene glycol is further preferred.
[0049] In addition, as a polyoxyalkylene polyol, two or more alkylene chains may be contained. Moreover, as polyurethane (A), it may be a structure which the structure derived from two or more different polyoxyalkylene polyols is combined with a polyisocyanate in between.
[0050] The number average molecular weight of the polyoxyalkylene polyol is preferably 300 to 1800, more preferably 330 to 1500, and further preferably 360 to 1200. If the number average molecular weight of the polyoxyalkylene polyol is 300 or more, the peeling force when peeling the protective sheet from the adherend can be reduced. If the number average molecular weight of the polyoxyalkylene polyol is 1800 or less, the weight average molecular weight of the polyurethane (A) can be low-molecular weight to obtain an adhesive layer with good hardness. Therefore, when an external impact is applied to the protective sheet, the force applied during cutting, pasting, and peeling operations can reduce the occurrence of cutting chips and breakage.
[0051] The hydroxyl value of the polyoxyalkylene polyol is preferably 30 to 400 mgKOH / g, more preferably 50 to 350 mgKOH / g, and further preferably 80 to 300 mgKOH / g. If the hydroxyl value is 30 mgKOH / g or more, there is an advantage that the generation of cutting scraps during cutting can be reduced. If the hydroxyl value is 300 mgKOH / g or less, there is an advantage that a cured product with moderate adhesion can be obtained. It should be noted that the hydroxyl value is measured by the method of method B according to JIS K1557-1.
[0052] As other preferred examples of polyols, from the viewpoint of reducing the peeling force when the protective sheet is peeled off from the adherend, polyols containing ethylenically unsaturated groups can be cited. In particular, under any of the following conditions, polyols containing ethylenically unsaturated groups are preferably included as polyols. The above conditions are conditions that require lower peeling from the viewpoint of the strength of the adherend, such as the miniaturization and filmization of the adherend, or conditions that are prone to cutting scraps and breakage due to high peel strength and insufficient crosslinking and cohesive strength of the adhesive layer.
[0053] As the ethylenically unsaturated group possessed by the polyol containing ethylenically unsaturated groups, (meth) acryloyloxy, vinyl, allyl etc. can be enumerated, and it is preferred that (meth) acryloyloxy is considered from the viewpoint of reducing the peeling force.By using the polyol containing ethylenically unsaturated groups, it is possible to also import ethylenically unsaturated groups at the position (in the molecular chain) outside the end of polyurethane (A).Thus, it is possible to reduce the peel strength of the adhesive layer, particularly the peel strength during the high-speed peeling.In addition, by the raising of the cross-linking density and the cohesive force of the adhesive layer, it is possible to suppress the cutting off of scraps and the damage.
[0054] The (meth)acryloyloxy group-containing polyol can be obtained, for example, by subjecting an epoxy group of an epoxy compound containing a (meth)acryloyloxy group to an acid catalyst cleavage reaction to synthesize a compound having two hydroxyl groups.
[0055] Examples of the epoxy compound containing a (meth)acryloyloxy group include glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, (meth)acrylate having an alicyclic epoxy group and a lactone adduct thereof, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, epoxides of dicyclopentenyl (meth)acrylate, and epoxides of dicyclopentenyloxyethyl (meth)acrylate.
[0056] As the (meth)acryloyloxy group-containing polyol, a compound obtained by adding a carboxyl group-containing ethylenically unsaturated compound such as (meth)acrylic acid to a polyepoxy compound such as 1,6-hexanediol diglycidyl ether may be used.
[0057] Commercially available polyols containing a (meth)acryloyloxy group may be used. Examples of the commercially available polyols include glycerol monomethacrylate (Brenma (registered trademark) GLM manufactured by NOF Corporation) obtained by cleaving the epoxy group of glycidyl methacrylate, and acrylic acid adduct of 1,6-hexanediol diglycidyl ether (Showa Denko K.K., LPOKISHI (trademark) SP-16LDA).
[0058] These polyols can be used alone or in combination of two or more. From the viewpoint of achieving a balance between multiple properties such as suppressing the generation of cutting scraps during cutting and reducing peeling force, it is preferred to use a polyol containing an ethylenically unsaturated group and a polyoxyalkylene polyol in combination. The ratio (molar ratio) of the polyol containing an ethylenically unsaturated group / polyoxyalkylene polyol is preferably 0.03 to 0.8, more preferably 0.08 to 0.7, further preferably 0.1 to 0.6, and particularly preferably 0.1 to 0.4.
[0059] "Polyisocyanate"
[0060] The polyisocyanate used in the present embodiment is not particularly limited as long as it does not have a hydroxyl group and is a compound having two or more isocyanate groups. From the perspective of suppressing gelation during synthesis and making it possible to uniformly extend the polymer, the number of isocyanate groups possessed by the polyisocyanate is preferably two.
[0061] Examples of the polyisocyanate include polyisocyanates that do not contain an ethylenically unsaturated group, such as toluene diisocyanate and hydrides thereof, xylylene diisocyanate and hydrides thereof, diphenylmethane diisocyanate and hydrides thereof, 1,5-naphthalene diisocyanate and hydrides thereof, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, tetramethylxylylene diisocyanate, isophorone diisocyanate, 4,4′-dicyclohexyl diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and norbornane diisocyanate. Among them, from the viewpoint of easy reaction control during synthesis of polyurethane (A) and imparting rigidity to the adhesive, a polyisocyanate having a cyclic hydrocarbon structure is preferred, more preferably at least one selected from isophorone diisocyanate, 4,4′-dicyclohexyl diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, and norbornane diisocyanate, and even more preferably isophorone diisocyanate.
[0062] From the viewpoint of reducing the peeling force when the protective sheet is peeled off from the adherend, the polyisocyanate preferably includes a polyisocyanate containing an ethylenically unsaturated group. In particular, under any of the following conditions, it is preferred to include a polyol containing an ethylenically unsaturated group as a polyol. The above conditions are the conditions for requiring lower peeling from the viewpoint of the strength of the adherend, such as the micronization and filmization of the adherend, and the conditions for the easy occurrence of cutting chips and breakage due to the high peel strength and insufficient crosslinking and cohesive force of the adhesive layer. As the ethylenically unsaturated group possessed by the polyisocyanate containing an ethylenically unsaturated group, (meth) acryloyloxy, vinyl, allyl, etc. can be cited. From the viewpoint of reducing the peeling force, it is preferred to consider (meth) acryloyloxy. By using a polyisocyanate containing an ethylenically unsaturated group, an ethylenically unsaturated group can also be introduced into the position (in the molecular chain) except the end of the polyurethane (A). Thus, the peeling strength of the adhesive layer can be reduced, and in particular, the peeling strength during high-speed peeling can be reduced. In addition, by improving the crosslinking density and cohesive force of the adhesive layer, cutting chips and breakage can be suppressed.
[0063] As the polyisocyanate containing (meth)acryloyloxy, for example, the reactant of (meth)acrylate and polyisocyanate containing hydroxyl can be mentioned. It can be obtained by carrying out urethanization and allophanation according to the method described in Japanese Patent Publication No. 2002-533542, Japanese Patent Publication No. 2012-111851, etc., synthesizing into a compound with allophanate bond. Specifically, as the (meth)acrylate containing hydroxyl, the same material as the (meth)acrylate containing hydroxyl illustrated as the ethylenically unsaturated compound containing hydroxyl as the raw material of polyurethane (A) described later can be mentioned. As polyisocyanate, the same material as the above-mentioned compound can be mentioned. Among them, it is preferably a compound containing allophanate bond obtained by reacting (meth)acrylate containing hydroxyl and diisocyanate under the condition of excess diisocyanate. More preferably, it is a compound containing an allophanate bond obtained by reacting a hydroxyalkyl (meth)acrylate with an alkylene diisocyanate under conditions in which the alkylene diisocyanate is in excess. In addition, it is further preferred to react one or more selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate with one or more selected from 1,6-hexamethylene diisocyanate and trimethylhexamethylene diisocyanate to form an allophanate.
[0064] Commercially available polyisocyanates containing a (meth)acryloyloxy group may be used, and examples of the commercially available polyisocyanates include Laromer (registered trademark) PR9000 manufactured by BASF, which is a reaction product of 2-hydroxyethyl acrylate and hexamethylene diisocyanate and contains an allophanate bond.
[0065] These polyisocyanates may be used alone or in combination of two or more.
[0066] From the viewpoint of achieving a balance between multiple properties such as suppressing the generation of cutting scraps during cutting and reducing the peeling force, it is preferred to use a polyisocyanate containing an ethylenically unsaturated group and a polyisocyanate not containing an ethylenically unsaturated group in combination. The ratio (molar ratio) of polyisocyanate containing an ethylenically unsaturated group / polyisocyanate not containing an ethylenically unsaturated group is preferably 0.03 to 0.8, more preferably 0.08 to 0.7, further preferably 0.1 to 0.6, and particularly preferably 0.1 to 0.4.
[0067] When obtaining an isocyanate-terminated urethane prepolymer, the total amount of the isocyanate groups of the polyisocyanate is preferably 1.05 to 1.8 mol, more preferably 1.1 to 1.7, and even more preferably 1.15 to 1.6, relative to 1 mol of the total amount of the hydroxyl groups of the polyol. If the total amount of the isocyanate groups is 1.05 mol or more, the weight average molecular weight of the polyurethane (A) is within an appropriate range.
[0068] In the case of obtaining a hydroxyl-terminated urethane prepolymer, the total amount of hydroxyl groups of the polyol is preferably 1.05 to 1.8 mol, more preferably 1.1 to 1.7, and even more preferably 1.15 to 1.6, relative to 1 mol of the total amount of isocyanate groups of the polyisocyanate. If the total amount of hydroxyl groups is 1.05 mol or more, the weight average molecular weight of the polyurethane (A) is within an appropriate range.
[0069] [Hydroxyl-containing ethylenically unsaturated compounds]
[0070] The ethylenically unsaturated compound containing a hydroxyl group is not particularly limited as long as it does not have an isocyanate group. The compound having a hydroxyl group and an ethylenically unsaturated group is not particularly limited. From the viewpoint of curability, the ethylenically unsaturated group is preferably at least one selected from a vinyl group, an allyl group, and a (meth)acryloyloxy group, preferably a (meth)acryloyloxy group.
[0071] "Hydroxy-containing (meth)acrylate"
[0072] The ethylenically unsaturated compound containing a hydroxyl group of the present embodiment is preferably a (meth)acrylate containing a hydroxyl group. As a (meth)acrylate containing a hydroxyl group, there is no particular limitation as long as it is a compound having a hydroxyl group and a (meth)acryloyloxy group without an isocyanate group. For example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; monoalcohols with (meth)acryloyl groups derived from various polyols such as 1,3-butanediol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, and 3-methylpentanediol mono(meth)acrylate, etc. are mentioned. From the perspective of reactivity with the isocyanate group of polyisocyanates and the photocurability of adhesive compositions, hydroxyalkyl (meth)acrylates are preferred, and hydroxyalkyl (meth)acrylates having an alkyl group with 2 to 6 carbon atoms are more preferred, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are more preferred. They can be used alone or in combination of two or more.
[0073] "Compounds having a hydroxyl group and a vinyl group"
[0074] The hydroxyl group-containing ethylenically unsaturated compound of this embodiment may be a compound having no isocyanate group but having a hydroxyl group and a vinyl group. Examples of the compound having a hydroxyl group and a vinyl group include polyalkylene glycol monovinyl ether, hydroxyalkyl vinyl ether, hydroxycarboxylic acid vinyl ester, and hydroxyalkyl vinyl ester.
[0075] Examples of the polyalkylene glycol monovinyl ether include diethylene glycol monovinyl ether and triethylene glycol monovinyl ether.
[0076] Examples of the hydroxyalkyl vinyl ether include 4-hydroxybutyl vinyl ether and 4-hydroxycyclohexyl vinyl ether.
[0077] Examples of the hydroxycarboxylic acid vinyl esters include vinyl glycolate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxycaproate, and 4-hydroxycyclohexylvinyl acetate.
[0078] Examples of the hydroxyalkyl vinyl ester include hydroxycyclohexyl vinyl carboxylate and the like.
[0079] "Compounds having a hydroxyl group and an allyl group"
[0080] The hydroxyl group-containing ethylenically unsaturated compound of the present embodiment may be a compound having no isocyanate group and having a hydroxyl group and an allyl group. Examples of the compound having a hydroxyl group and an allyl group include hydroxyalkyl allyl ether, hydroxycarboxylic acid allyl ester, and hydroxyalkyl allyl ester.
[0081] Examples of the hydroxyalkyl allyl ether include 2-hydroxyethyl allyl ether, 4-hydroxybutyl allyl ether, glycerol monoallyl ether, and 4-hydroxycyclohexyl allyl ether.
[0082] Examples of the allyl hydroxycarboxylate include allyl hydroxyacetate, allyl hydroxypropionate, allyl hydroxybutyrate, allyl hydroxyhexanoate, and allyl 4-hydroxycyclohexylacetate.
[0083] Examples of the hydroxyalkyl allyl ester include hydroxyethyl allyl ester, hydroxypropyl allyl ester, hydroxybutyl allyl ester, hydroxyisobutyl allyl ester, and hydroxycyclohexyl allyl ester.
[0084] The ratio of the above-mentioned ethylenically unsaturated compound containing hydroxyl is preferably set in a manner that the total amount of the hydroxyl groups of the polyol and the ethylenically unsaturated compound containing hydroxyl is equal to the total amount of the isocyanate groups of the polyisocyanate. The so-called equal means that the difference between the moles is preferably less than 0.05 mole, more preferably less than 0.01 mole. If the difference between the moles is less than 0.05 mole, then the unreacted monomers can be fully reduced, and the unreacted hydroxyl and isocyanate groups can also be fully reduced, so when a cured product is made, the change of the gel fraction over time can also be suppressed.
[0085] [Ethylenically unsaturated compound containing an isocyanate group]
[0086] As the ethylenically unsaturated compound containing an isocyanate group, as long as it does not have a hydroxyl group, the compound having an isocyanate group and an ethylenically unsaturated group is not particularly limited. Preferably, the ethylenically unsaturated compound containing an isocyanate group is a (meth) acrylate containing an isocyanate group. For example, isocyanate alkyl (meth) acrylates such as 2-isocyanate ethyl (meth) acrylate, 2-isocyanate propyl (meth) acrylate, 4-isocyanate butyl (meth) acrylate, and 6-isocyanate hexyl (meth) acrylate can be cited. From the perspective of reactivity with the hydroxyl group of the polyoxyalkylene polyol (a1) and the photocurability of the adhesive composition, isocyanate alkyl (meth) acrylates having an alkyl group of 2 to 6 carbon atoms are preferred, and 2-isocyanate ethyl (meth) acrylate and 4-isocyanate butyl (meth) acrylate are more preferred. They can be used alone or in combination of two or more.
[0087] The ratio of the above-mentioned ethylenically unsaturated compound containing isocyanate group is preferably set in a manner that the total amount of the isocyanate group of the polyisocyanate and the isocyanate group of the ethylenically unsaturated compound containing isocyanate group is equal to the total amount of the hydroxyl group of the polyol. The so-called equal means that the difference in the number of moles of the two is preferably 0.05 mole or less, more preferably 0.01 mole or less. If the difference in the number of moles of the two is 0.05 mole or less, then the unreacted monomer can be fully reduced, and the unreacted hydroxyl and isocyanate group amounts can also be fully reduced, so when a cured product is made, the change in the gel fraction over time can also be suppressed.
[0088] The weight average molecular weight of polyurethane (A) is 3000 to 30000, preferably 5000 to 28000, and more preferably 6000 to 25000. If the weight average molecular weight is 3000 or more, the cured product of the adhesive composition has sufficient flexibility, and the protective sheet having the cured product as the adhesive layer has sufficient lamination. If the weight average molecular weight is 30000 or less, it has a moderate hardness when the adhesive layer is made, suppresses the generation of cutting scraps during cutting, and can reduce the damage of the adhesive layer, the damage of the adherend, and the pollution when an external impact is applied. The weight average molecular weight of polyurethane (A) can be in the range of 3000 or more and less than 10000. In this case, since the proportion of polyurethane (A) in the adhesive composition can be large while maintaining the coating property of the adhesive composition, the surface strength of the coating film is high.
[0089] The carbamate bond concentration of polyurethane (A) is preferably 1.0 to 5 mol / kg, more preferably 1.5 to 5 mol / kg, and further preferably 1.85 to 3.5 mol / kg. If the carbamate bond concentration is 1.0 mol / kg or more, the adhesive layer has a moderate elongation, and an adhesive layer with good hardness and tensile strength is obtained. If the carbamate bond concentration is 5 mol / kg or less, the protective sheet has good low peelability, and the damage of the adherend can be prevented when it is peeled from the adherend.
[0090] The ethylenically unsaturated group equivalent of polyurethane (A) is preferably 900 to 3000 g / mol, more preferably 950 to 2700 g / mol, further preferably 1000 to 2500 g / mol, and further preferably 1100 to 2300 g / mol. If the ethylenically unsaturated group equivalent is 900 g / mol or more, the softness and elongation of the adhesive layer are good. If the ethylenically unsaturated group equivalent is 3000 g / mol or less, the hardness and tensile strength of the adhesive layer are good.
[0091] The lower limit of the ethylenically unsaturated group equivalent of polyurethane (A) is preferably more than 900g / mol, more preferably more than 950g / mol, more preferably more than 1000g / mol, and more preferably more than 1100g / mol. If the ethylenically unsaturated group equivalent is more than 900g / mol, the softness and elongation of the adhesive layer are good. The upper limit of the ethylenically unsaturated group equivalent of polyurethane (A) is preferably less than 3000g / mol, more preferably less than 2700g / mol, more preferably less than 2500g / mol, and more preferably more than 2300g / mol. If the ethylenically unsaturated group equivalent is less than 3000g / mol, the hardness and tensile strength of the adhesive layer are good.
[0092] The above upper limit values and lower limit values may be arbitrarily combined.
[0093] The content of polyurethane (A) is preferably 10 to 90% by mass, more preferably 25 to 80% by mass, further preferably 35 to 75% by mass, and further preferably 40 to 70% by mass, relative to the total of 100% by mass of polyurethane (A) and monomer (B) containing an ethylenically unsaturated group. If the content of polyurethane (A) is 10% by mass or more, the elongation and tensile strength of the adhesive layer are good. If the content of polyurethane (A) is 90% by mass or less, the low peelability as a protective sheet is good.
[0094] The lower limit of the content of polyurethane (A) is preferably 10% by mass or more, more preferably 25% by mass or more, further preferably 35% by mass or more, and further preferably 40% by mass or more, relative to the total of 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. If the content of polyurethane (A) is 10% by mass or more, the elongation and tensile strength of the adhesive layer are good.
[0095] The upper limit of the content of polyurethane (A) is preferably 90% by mass or less, more preferably 80% by mass or less, further preferably 75% by mass or less, and further preferably 70% by mass or less, relative to the total of 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. If the content of polyurethane (A) is 90% by mass or less, the low peelability as a protective sheet is good.
[0096] The above upper limit values and lower limit values may be arbitrarily combined.
[0097] [Ethylenically unsaturated group-containing monomer (B)]
[0098] The monomer (B) containing an ethylenically unsaturated group is not particularly limited as long as it is a monomer having an ethylenically unsaturated group. From the viewpoint of curability, it is preferably a vinyl group or a (meth) acryloyl group, and more preferably a (meth) acryloyl group. Among them, from the viewpoints of the dilutability of the adhesive composition, the punching processability of the protective sheet, and the reduction of cutting scraps during cutting, the monomer (B) containing an ethylenically unsaturated group preferably contains a monofunctional (meth) acrylate (B1). Furthermore, from the viewpoints of the low peelability of the protective sheet, the improvement of hardness, and the tensile strength, the monomer (B) containing an ethylenically unsaturated group may also contain a multifunctional (meth) acrylate (B2) as needed. The so-called "monofunctional" refers to having only one (meth) acryloyloxy group, and the so-called "multifunctional" refers to having multiple (meth) acryloyloxy groups.
[0099] Examples of the monofunctional (meth)acrylate (B1) include alkyl (meth)acrylates, cyclic alkyl (meth)acrylates, alkoxyalkyl (meth)acrylates, alkoxy (poly)alkylene glycol (meth)acrylates, hydroxyl group-containing (meth)acrylates, carboxyl group-containing (meth)acrylates, fluoroalkyl (meth)acrylates, dialkylaminoalkyl (meth)acrylates, (meth)acrylamides, and epoxy group-containing (meth)acrylates.
[0100] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-hexyl (meth)acrylate, isooctyl (meth)acrylate, isostearyl (meth)acrylate, lauryl (meth)acrylate, and tridecyl (meth)acrylate.
[0101] Examples of the cyclic alkyl (meth)acrylate include cyclohexyl (meth)acrylate, norbornyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, and tricyclodecane dihydroxymethyl di(meth)acrylate.
[0102] Examples of the alkoxyalkyl (meth)acrylate include ethoxyethyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, 2-methoxyethoxyethyl (meth)acrylate, and 2-ethoxyethoxyethyl (meth)acrylate.
[0103] Examples of the alkoxy (poly) alkylene glycol (meth)acrylate include methoxydiglycol (meth)acrylate, ethoxydiglycol (meth)acrylate, and methoxydipropylene glycol (meth)acrylate.
[0104] Examples of the hydroxyl group-containing (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1,3-butanediol (meth)acrylate, 1,4-butanediol (meth)acrylate, 1,6-hexanediol (meth)acrylate, and 3-methylpentanediol (meth)acrylate.
[0105] As a carboxyl group-containing (meth)acrylate, (meth)acrylic acid, β-carboxyethyl (meth)acrylate, etc. are mentioned, for example.
[0106] As fluoroalkyl (meth)acrylate, octafluoropentyl (meth)acrylate etc. are mentioned, for example.
[0107] As a dialkylaminoalkyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, etc. are mentioned, for example.
[0108] Examples of the (meth)acrylamide include (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropylacrylamide, N-hexyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, (meth)acryloylmorpholine, and diacetoneacrylamide.
[0109] As an epoxy group-containing (meth)acrylate, glycidyl (meth)acrylate etc. are mentioned, for example.
[0110] Among them, from the viewpoint of reducing the cutting scraps when the protective sheet is cut, alkyl (meth)acrylates are preferred, and chain alkyl (meth)acrylates are more preferred, wherein the carbon number of the chain alkyl group is 6 to 18. More specifically, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, isooctyl (meth)acrylate, isostearyl (meth)acrylate, and isobornyl (meth)acrylate are preferred, and 2-ethylhexyl (meth)acrylate and lauryl (meth)acrylate are more preferred. In addition, the monofunctional (meth)acrylate (B1) may be composed of one compound or two or more compounds.
[0111] As the polyfunctional (meth)acrylate (B2), an ester compound of a polyol compound and (meth)acrylic acid is preferred, and a tri- to hexa-functional (meth)acrylate is more preferred. For example, polyethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, 1,3-bis(hydroxyethyl)-5,5-dimethylhydantoin di(meth)acrylate, α,ω-di(meth)acryloylbisdiethylene glycol phthalate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxylate tri(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, diacryloyloxyethyl phosphate, dipentaerythritol trihydroxy(meth)acrylate, pentaerythritol tetra(meth)acrylate, and the like can be mentioned.
[0112] Among them, from the viewpoint of suppressing the peel strength of the protective sheet to be low, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxylate tri(meth)acrylate, dipentaerythritol trihydroxy(meth)acrylate, pentaerythritol tetra(meth)acrylate are more preferred, and trimethylolpropane tri(meth)acrylate and trimethylolpropane ethoxylate tri(meth)acrylate are further preferred. In addition, the multifunctional (meth)acrylate (B2) may be composed of one compound or may be composed of two or more compounds.
[0113] The monomer (B) containing an ethylenically unsaturated group may also contain a monomer (B3) containing an ethylenically unsaturated group other than the components (B1) (B2). Examples of the monomer (B3) containing an ethylenically unsaturated group other than the components (B1) (B2) include acrylonitrile, methacrylonitrile, styrene, α-methylstyrene, vinyl acetate, vinyl propionate, vinyl stearate, vinyl chloride, 1,1-dichloroethylene, alkyl vinyl ether, vinyl toluene, N-vinyl pyridine, N-vinyl pyrrolidone, dialkyl itaconate, dialkyl fumarate, allyl alcohol, hydroxybutyl vinyl ether, hydroxyethyl vinyl ether, 4-hydroxymethylcyclohexyl methyl vinyl ether, triethylene glycol monovinyl ether or diethylene glycol monovinyl ether, methyl vinyl ketone, N-acrylamidomethyltrimethylammonium chloride, allyltrimethylammonium chloride, dimethylallyl vinyl ketone, and the like.
[0114] The content of the monomer (B) containing an ethylenically unsaturated group is preferably 10 to 90% by mass relative to the total 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group, more preferably 20 to 75% by mass, further preferably 25 to 65% by mass, and further preferably 30 to 60% by mass. If the content of the monomer (B) containing an ethylenically unsaturated group is more than 10% by mass, the low peelability as a protective sheet is good. If the content of the monomer (B) containing an ethylenically unsaturated group is less than 90% by mass, the elongation and tensile strength of the adhesive layer are good.
[0115] The lower limit of the content of the monomer (B) containing an ethylenically unsaturated group is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 25% by mass or more, and further preferably 30% by mass or more, relative to the total of 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. If the content of the monomer (B) containing an ethylenically unsaturated group is 10% by mass or more, the low peelability as a protective sheet is good.
[0116] The upper limit of the content of the monomer (B) containing an ethylenically unsaturated group is preferably 90% by mass or less, more preferably 75% by mass or less, further preferably 65% by mass or less, and further preferably 60% by mass or less, relative to the total of 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. If the content of the monomer (B) containing an ethylenically unsaturated group is 90% by mass or less, the low peelability as a protective sheet is good.
[0117] The above upper limit values and lower limit values may be arbitrarily combined.
[0118] In the case where the monomer (B) containing an ethylenically unsaturated group contains a monofunctional (meth) acrylate (B1) and a multifunctional (meth) acrylate (B2), the content of the monofunctional (meth) acrylate (B1) is preferably 5 to 89% by mass, more preferably 15 to 74% by mass, and further preferably 25 to 57% by mass relative to the total of 100% by mass of the above-mentioned polyurethane (A) and the above-mentioned monomer (B) containing an ethylenically unsaturated group. If the content of the monofunctional (meth) acrylate (B1) is 5% by mass or more, the low peelability as a protective sheet is good. If the content of the monofunctional (meth) acrylate (B1) is 89% by mass or less, the adhesive becomes a moderate viscosity, and the coating when making the adhesive sheet becomes easy. The content of the multifunctional (meth) acrylate (B2) is preferably 0.1 to 30% by mass, more preferably 1 to 20% by mass, and further preferably 3 to 15% by mass relative to the total of 100% by mass of the above-mentioned polyurethane (A) and the above-mentioned monomer (B) containing an ethylenically unsaturated group. If the content of the monofunctional (meth)acrylate (B1) is 0.1% by mass or more, the generation of cutting scraps and the damage of the adhesive layer are suppressed, and the low peelability as a protective sheet is good. If the content of the monofunctional (meth)acrylate (B1) is 30% by mass or less, the elongation of the adhesive layer is good.
[0119] [Photopolymerization initiator (C)]
[0120] The photopolymerization initiator (C) is not particularly limited as long as it is a polymerization initiator that generates radicals by light irradiation, and examples thereof include carbonyl-based photopolymerization initiators, sulfide-based photopolymerization initiators, acylphosphine oxides, quinone-based photopolymerization initiators, sulfonyl chloride-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.
[0121] Examples of the carbonyl photopolymerization initiator include benzophenone, benzyl, benzoin, ω-bromoacetophenone, chloroacetone, acetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, p-dimethylaminoacetophenone, p-dimethylaminoacetophenone, 2-chlorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-bis(diethylaminobenzophenone), Michler's ketone, benzoin methyl ether, and benzoin isobutyl ether. ether, benzoin-n-butyl ether, benzyl methyl ketal, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, methyl benzoyl formate, 2,2-diethoxyacetophenone, 4-N,N'-dimethylacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, etc.
[0122] Examples of the sulfide-based photopolymerization initiator include diphenyl disulfide, dibenzyl disulfide, tetraethylthiuram disulfide, and tetramethylammonium monosulfide.
[0123] Examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide.
[0124] Examples of the quinone-based photopolymerization initiator include quinone-based photopolymerization initiators such as benzoquinone and anthraquinone.
[0125] Examples of the sulfonyl chloride-based photopolymerization initiator include 2-naphthalenesulfonyl chloride and the like.
[0126] Examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, and 2-methylthioxanthone.
[0127] Among these exemplified compounds, carbonyl photopolymerization initiators and acylphosphine oxides are preferred from the perspective of transparency of the adhesive layer obtained by curing the adhesive composition, and 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyldiphenylphosphine oxide are more preferred. In addition, the photopolymerization initiator (C) may be composed of one compound or two or more compounds.
[0128] The content of the photopolymerization initiator (C) is preferably 0.05 to 5 parts by mass, more preferably 0.1 to 3 parts by mass, and further preferably 0.3 to 1 part by mass, relative to 100 parts by mass of the total of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. If the content of the photopolymerization initiator (C) is 0.05 parts by mass or more, the adhesive composition has sufficient photocurability. If the content of the photopolymerization initiator (C) is 5 parts by mass or less, contamination of the adherend when the protective sheet is peeled off can be suppressed.
[0129] [Plasticizer (D)]
[0130] The plasticizer (D) may be any known material without particular limitation. For example, fatty acid esters may be preferably used. The plasticizer (D) may improve the lamination property (wettability) and degassing property (ease of removing bubbles trapped during lamination) of the protective sheet.
[0131] Examples of fatty acid esters include esters of monobasic acids or polybasic acids having 8 to 18 carbon atoms and branched alcohols having 18 or less carbon atoms, and esters of unsaturated fatty acids or branched acids having 14 to 18 carbon atoms and tetravalent alcohols. Specific examples of preferred fatty acid esters include ethylhexyl stearate.
[0132] When a plasticizer (D) is used, the content is preferably 1 to 30 parts by mass, more preferably 5 to 25 parts by mass, and further preferably 10 to 23 parts by mass relative to a total of 100 parts by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. If the content of the plasticizer (D) is 1 part by mass or more, the effects of adding the plasticizer (D) such as improved laminar properties (wettability) and improved defoaming properties (ease of removing bubbles trapped during lamination) of the protective sheet can be fully expected. If the content of the plasticizer (D) is 30 parts by mass or less, the contamination of the adherend when the protective sheet is peeled off can be fully suppressed.
[0133] [Solvent]
[0134] Since the adhesive composition of the present embodiment contains a monomer (B) containing an ethylenically unsaturated group as a low molecular weight component, it can be adjusted to a viscosity that can be applied even without adding a solvent. That is, the adhesive composition may also be substantially free of solvent. In this case, when manufacturing a protective sheet, the process of heating and drying the solvent can be omitted, and productivity becomes higher. In particular, when manufacturing a protective sheet with a film thickness exceeding 50 μm, it is preferred that the adhesive composition substantially does not contain the solvent. The meaning of "substantially free of" in the present invention is that the content of the above-mentioned solvent in the adhesive composition of the present invention is 0 to 1% by mass, preferably 0 to 0.5% by mass or less, and more preferably 0 to 0.1% by mass or less.
[0135] A solvent may be added to the adhesive composition for the purpose of adjusting the viscosity during coating. The solvent can be appropriately selected according to other components contained in the adhesive composition, but an organic solvent is preferred. The organic solvent used is not particularly limited, and examples thereof include methyl ethyl ketone, acetone, ethyl acetate, tetrahydrofuran, dihydrofuran, and dihydrofuran. Alkane, cyclohexanone, n-hexane, toluene, xylene, n-propyl alcohol, isopropyl alcohol etc. These organic solvents can be used alone, and in addition, two or more kinds can be mixed and used. The solvent is preferably removed by drying after the adhesive composition is applied to a substrate, and then photocured.
[0136] In addition, other additives may be added to the adhesive composition as required without damaging transparency. Examples of additives include surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, light stabilizers such as benzotriazole, phosphates and other flame retardants, antistatic agents such as surfactants, dyes, etc.
[0137] It should be noted that, here, an example of a method for synthesizing a polyurethane (A) containing an ethylenically unsaturated group is described, but the monomer (B) containing an ethylenically unsaturated group and other components contained in the adhesive composition vary depending on the type of compound used, and commercially available products can be used, so the description of the synthesis method is omitted.
[0138] <Method for synthesizing polyurethane (A)>
[0139] Hereinafter, an example of a preferred synthesis method of the polyurethane (A) contained in the adhesive composition of the present embodiment is described, but the synthesis method of the polyurethane (A) is not limited thereto and can be appropriately changed according to the conditions such as the raw materials and equipment used for the synthesis. In addition, in this example, the reaction of the hydroxyl group and the isocyanate group is carried out in any process in the presence of an organic solvent that is inactive to the isocyanate group, using a carbamate catalyst such as dibutyltin dilaurate, dibutyltin diethylhexanoate, and dioctyltin dilaurate. The reaction is preferably carried out continuously at 30 to 100° C. for 1 to 5 hours. The amount of the carbamate catalyst used is preferably 50 to 500 mass ppm relative to the total mass of the reactants.
[0140] <First Synthesis Method>
[0141] First, polyol and polyisocyanate are added in a ratio where the amount of isocyanate groups (number basis, the same below) is greater than the amount of hydroxyl groups (number basis, the same below), and they are reacted to synthesize a urethane prepolymer having an isocyanate group at the end. Specific examples of polyol and polyisocyanate are as exemplified in the section of polyurethane (A).
[0142] At this time, in the case of using a polyisocyanate containing an ethylenically unsaturated group and a polyisocyanate not containing an ethylenically unsaturated group as a polyisocyanate, it can be added simultaneously, or it can be added separately, and the order of addition can also be arbitrary. The introduction position of the ethylenically unsaturated group in the main chain of polyurethane (A) can also be adjusted in the order of adding a polyisocyanate containing an ethylenically unsaturated group and a polyisocyanate not containing an ethylenically unsaturated group. From the viewpoint of making the distance between the crosslinking points of polyurethane (A) short and the adhesive layer low in peeling, it is preferred to also introduce an ethylenically unsaturated group near the center of the main chain. That is, it is preferred that the polyisocyanate containing an ethylenically unsaturated group is added first or the polyisocyanate containing an ethylenically unsaturated group and the polyisocyanate not containing an ethylenically unsaturated group are added simultaneously, and it is more preferred that the polyisocyanate containing an ethylenically unsaturated group is added first.
[0143] Similarly, when a polyoxyalkylene polyol and a polyol containing an ethylenically unsaturated group are used as the polyol, they may be added simultaneously or separately, and the order of addition may be arbitrary. From the viewpoint of reducing the peeling of the adhesive layer, it is preferred to add the polyol containing an ethylenically unsaturated group first, or to add the polyol containing an ethylenically unsaturated group and the polyoxyalkylene polyol simultaneously, and it is more preferred to add the polyol containing an ethylenically unsaturated group first.
[0144] Next, the isocyanate group-containing urethane prepolymer is reacted with the hydroxyl group-containing ethylenically unsaturated compound to synthesize a polyurethane (A) having an ethylenically unsaturated group introduced at the molecular chain terminal.
[0145] Preferably, on a number basis, 90 to 100% of the ends of the polyurethane contained in the polyurethane (A) containing an ethylenically unsaturated group are introduced with an ethylenically unsaturated group, more preferably 95 to 100%, and further preferably 100%. If the amount of the ethylenically unsaturated group introduced is 90% or more relative to the isocyanate group on a number basis, the cohesive force of the adhesive layer obtained by curing the adhesive composition is fully obtained. The ratio of the number of ends introduced with an ethylenically unsaturated group to the number of ends of all polyurethane molecular chains can be measured by IR, NMR, etc.
[0146] <Second Synthesis Method>
[0147] First, polyol and polyisocyanate are added in a ratio in which the amount of hydroxyl groups (number basis, the same below) is greater than the amount of isocyanate groups (number basis, the same below), and they are reacted to synthesize a urethane prepolymer having a hydroxyl group at the end. Specific examples of polyoxyalkylene polyol and polyisocyanate are as exemplified in the section of polyurethane (A).
[0148] Next, the hydroxyl group-containing urethane prepolymer is reacted with the isocyanate group-containing ethylenically unsaturated compound to synthesize a polyurethane (A) having an ethylenically unsaturated group introduced at the molecular chain terminal.
[0149] Preferably, 90 to 100% of the ends of the polyurethane contained in the polyurethane (A) are introduced with ethylenically unsaturated groups, more preferably 95 to 100%, and further preferably 100%, based on the number. If the amount of ethylenically unsaturated groups introduced is 90% or more relative to the hydroxyl groups based on the number, the cohesive force of the adhesive layer obtained by curing the adhesive composition is fully obtained. The ratio of the number of ends introduced with ethylenically unsaturated groups to the number of ends of all polyurethane molecular chains can be measured by IR, NMR, etc.
[0150] <Method for producing adhesive composition>
[0151] The adhesive composition is prepared by mixing a polyurethane (A) containing an ethylenically unsaturated group, a monomer (B) containing an ethylenically unsaturated group, a photopolymerization initiator (C), a plasticizer (D) as required, other additives, and an organic solvent. The mixing method is not particularly limited, and for example, a homogenizer or a stirring device equipped with stirring blades such as paddle blades can be used.
[0152] In addition, all the components can be added at once for mixing, or each component can be divided into multiple times for repeated addition and mixing. It should be noted that, in the case of a component that is solid at room temperature, the component is easily mixed in the adhesive composition with high uniformity by adding a substance dissolved in a solvent or a substance dispersed in a dispersion medium, or by heating and melting the substance.
[0153] <Protective sheet>
[0154] <Protective sheet composition>
[0155] The protective sheet involved in this embodiment includes a substrate and an adhesive layer, and an adhesive layer composed of a cured product of the adhesive composition is formed on one side of the substrate. The thickness of the adhesive layer is preferably 3 to 150 μm, more preferably 5 to 130 μm, and further preferably 10 to 100 μm. If the film thickness of the adhesive layer is 3 μm or more, the strength of the adhesive layer is sufficient, and if the film thickness is 150 μm or less, the film thickness of the adhesive layer is easy to control.
[0156] Furthermore, when it is desired to impart a function of protecting an adherend from impact (impact resistance) to the protective sheet, the thickness of the adhesive layer is preferably 50 μm or more.
[0157] The material of the substrate can be appropriately selected according to the purpose of the protective sheet, and a resin film can be cited as an example. When the protective sheet is used as a protective sheet for the display surface in the manufacturing process of optical components, etc., when inspecting the adherend, that is, the product for the presence or absence of scratches and foreign matter, the substrate is preferably transparent when the protective sheet is laminated. Examples of transparent substrates include polyethylene terephthalate, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, polyvinyl chloride, cellulose, etc.
[0158] The thickness of the substrate can be appropriately selected according to the purpose of the protective sheet and is not particularly limited. However, in the case of a resin film, the thickness of the substrate is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more from the viewpoint of operability and strength. In addition, if the flexibility of the resin film is taken into consideration, the thickness of the substrate is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 100 μm or less.
[0159] In addition, as the substrate, it is preferred to use a substance that has been subjected to an antistatic treatment. The antistatic treatment applied to the substrate is not particularly limited, and a method of providing an antistatic layer on at least one side of the substrate, a method of incorporating an antistatic agent into the substrate, etc. can be used. Furthermore, the surface of the substrate forming the adhesive layer can be subjected to an easy-adhesion treatment such as acid treatment, alkali treatment, primer treatment, corona treatment, plasma treatment, ultraviolet treatment, ozone treatment, etc. as required.
[0160] In the protective sheet, a release film may be laminated on the surface of the adhesive layer for the purpose of protecting the adhesive layer. As the material of the release film, for example, paper, plastic film, etc. may be used, but plastic film is suitable from the aspect of excellent surface smoothness. The plastic film used as the release film is not particularly limited as long as it can protect the above-mentioned adhesive layer, and for example, polyethylene, polypropylene, polyethylene terephthalate, polybutylene, etc. may be cited. In addition, it is preferably a material that has been subjected to an easy-to-peel treatment on the surface in contact with the adhesive layer.
[0161] <Method for producing protective sheet>
[0162] The manufacturing method of the protective sheet involved in the present embodiment can be obtained, for example, by coating an adhesive composition on a substrate, laminating a release film as needed, and then irradiating the adhesive composition with ultraviolet light to photocure it. The ultraviolet light can be irradiated from a transparent release film, or from the substrate side when the substrate is transparent.
[0163] The method for applying the adhesive composition to the substrate is not particularly limited and can be appropriately selected. For example, as the method for applying the adhesive composition to the substrate, methods using various coating machines such as a gravure roll coater, a reverse roll coater, a touch roll coater, a dip roll coater, a rod coater, a blade coater, a spray coater, a comma coater, a direct coater, and screen printing methods can be cited.
[0164] In addition, as the light source for photocuring the adhesive composition, black light, low-pressure mercury lamp, high-pressure mercury lamp, ultra-high-pressure mercury lamp, metal halide lamp, xenon lamp, etc. can be cited. The irradiation intensity of the light can be any light intensity as long as the adhesive composition can be sufficiently cured, for example, preferably 50 to 3000 mW / cm 2 It should be noted that if the light irradiation intensity is weak, curing takes time, so productivity decreases.
[0165] <Applications and required performance of protective sheets>
[0166] In the manufacturing process of optical components, etc., sometimes in the previous stage of laminating the protective sheet on the product or component, the protective sheet is cut according to the shape of the product or component. In addition, sometimes the product or component is laminated with the protective sheet, and the punching process is performed. In addition, the protective sheet is sometimes used appropriately for the purpose of protecting the surface of the plastic film used as an optical component. As the above-mentioned optical component, for example, polarizing plates, wavelength plates, phase difference plates, optical compensation films, reflective sheets, brightness enhancement films, etc. used in liquid crystal displays such as smart phones, personal computers, and televisions can be cited.
[0167] When the protective sheet involved in this embodiment is used as a protective sheet like these, in order to prevent contamination of the adherend, the protective sheet is required not to generate cutting scraps when cutting. In addition, it is also required to have a hardness and tensile strength to the extent that the adhesive layer and the adherend are not damaged when an external impact is applied or a force is applied when peeling.
[0168] In this case, it is preferred that the adhesive layer constituting the protective sheet has a hardness of a certain level or higher and has appropriate elongation and tensile strength.
[0169] From these viewpoints, the pencil hardness (coating surface strength) of the adhesive layer is preferably a hardness of 4B or more. The elongation at break of the adhesive layer is preferably 40 to 300%, preferably 50 to 300%, more preferably 92 to 300%, and further preferably 92 to 250%. The breaking strength (tensile strength) of the adhesive layer is preferably 100 to 800 g / mm 2 , more preferably 200 to 800 g / mm 2 , more preferably 300 to 800 g / mm 2 , and more preferably 330 to 600 g / mm 2 The specific methods for measuring these physical properties in the adhesive layer of the protective sheet will be described later in Examples.
[0170] In addition, when the protective sheet involved in the present embodiment is used as a protective sheet as described above, the protective sheet requires a minimum peel strength in order not to peel off from the product or component during operations such as transportation. On the other hand, when the protective sheet is peeled off from the product or component, in order to facilitate the peeling operation or to prevent the product or component from being deformed or damaged during peeling, the peel strength needs to be low. From these viewpoints, the peeling force of the protective sheet is preferably 0.1 to 10 gf / 25 mm, more preferably 0.2 to 8 gf / 25 mm, more preferably 0.2 to 3 gf / 25 mm, and even more preferably 0.2 to 1 gf / 25 mm when the peeling speed is 0.3 m / min, although it is also related to the thickness of the substrate and the adhesive layer. When the peeling speed is 2.4 m / min, although it also depends on the thickness of the substrate and the adhesive layer, it is preferably 1 to 50 gf / 25 mm, more preferably 1.5 to 40 gf / 25 mm, further preferably 1.5 to 10 gf / 25 mm, and further preferably 1.5 to 4.5 gf / 25 mm. The specific method for measuring the peel strength of the protective sheet will be described later in the Examples.
[0171] As mentioned above, the protective sheet is required to have multiple properties, and sometimes the optimal range of the required properties also changes depending on the thickness and type of the substrate and adhesive used in the protective sheet. For example, if the thickness of the substrate is thickened, or the pencil hardness of the substrate is changed to a high pencil hardness, the impact when the protective sheet is cut is easily transmitted to the adhesive layer, and cutting shavings are more likely to be generated. From this point of view, as the physical properties of the adhesive layer that further reduces the generation of cutting shavings, it is preferred that the elongation is more than 92%, the tensile strength is 300gf / mm 2 For example, when a (meth)acrylic acid alkyl ester as a monofunctional (meth)acrylate (B1) is used as the monomer (B) containing an ethylenically unsaturated group, if the alkyl chain contained in the (meth)acrylic acid alkyl ester is made longer, the elongation tends to be improved. From this viewpoint, it is preferred to use a (meth)acrylic acid chain alkyl ester having 8 to 18 carbon atoms in the chain alkyl group, more preferably to use a (meth)acrylic acid chain alkyl ester having 12 to 18 carbon atoms in the chain alkyl group, and further preferably to use lauryl (meth)acrylate.
[0172] In addition, by using polyoxyalkylene polyol as the polyol used for polyurethane (A), the number average molecular weight of polyoxyalkylene polyol is reduced, and the urethane bond concentration of polyurethane (A) is increased, thereby the elongation of the adhesive layer can also be improved. From this viewpoint, it is preferred to use polyoxyalkylene polyol with a number average molecular weight of 360 to 1200, and the urethane bond concentration of polyurethane (A) is preferably 1.9 to 5 mol / kg, more preferably 2 to 5 mol / kg, and further preferably 2.3 to 5 mol / kg.
[0173] On the other hand, if the elongation of the adhesive layer is increased, sometimes the peeling force is increased and it is easy to damage the adherend, or the tensile strength is reduced and the adhesive layer is damaged, or the adherend is contaminated when the protective sheet is peeled. From such a point of view, if a multifunctional (meth) acrylate (B2) is used as a monomer (B) containing an ethylenically unsaturated group, the adhesive layer can be low-peeled and hardness and tensile strength can be improved. In this case, since the elongation of the protective sheet is reduced due to the use of the multifunctional (meth) acrylate (B2), it is necessary to adjust the mixing amount of the multifunctional (meth) acrylate (B2) in the range of not less than 92% of the elongation of the protective sheet from the perspective of obtaining a balance between the performances of the two. In this case, the content of the multifunctional (meth) acrylate (B2) is preferably 0.1 to 15% by mass, more preferably 1 to 12% by mass, and more preferably 3 to 10% by mass relative to the total 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. Furthermore, various properties can be adjusted by adjusting the blending ratio of the polyurethane (A) and the monofunctional (meth)acrylate (B1).
[0174] From the viewpoint of reducing the generation of cutting shavings while achieving a balance of various properties, it is preferred that the polyurethane (A) is 50% by mass or more relative to the total 100% by mass of the polyurethane (A) and the monomer (B) containing an ethylenically unsaturated group. In the above range, if the monofunctional (meth) acrylate (B1) is increased, the elongation of the adhesive layer increases and the peeling force tends to be low. If the polyurethane (A) is increased, the hardness and strength of the adhesive layer tend to increase. From the viewpoint of achieving a balance of various properties that does not depend on the type of substrate and suppressing the generation of cutting shavings, the content of polyurethane (A) is preferably 50 to 70% by mass, and the content of monofunctional (meth) acrylate (B1) is preferably 20 to 50% by mass.
[0175] Example
[0176] Hereinafter, the present invention will be described in more detail by way of Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0177] <Synthesis of polyurethane (A)>
[0178] (Synthesis example 1)
[0179] In a four-necked flask equipped with a thermometer, a stirrer, a dropping funnel, and a cooling tube with a drying tube, 2 mol of polypropylene glycol D-1000 (manufactured by Mitsui Chemicals, number average molecular weight 1000) with a hydroxyl value of 111 mgKOH / g and a hydroxyl group at the end, 3 mol of isophorone diisocyanate (Desmodiure I, manufactured by Sumika Cobestrower) were added, and the temperature was raised to 80°C and reacted for 7 hours. 2 mol of 2-hydroxyethyl acrylate was added to the obtained urethane prepolymer. Then, it was reacted at 80°C for 2 hours to obtain a polyurethane (Ai) with an acryloyloxy group at the end. The polyurethane (Ai) was analyzed by IR, and it was confirmed that the peak derived from the isocyanate group disappeared. The weight average molecular weight of the obtained polyurethane (Ai) was 7,000. The weight average molecular weight, the urethane bond concentration, and the ethylenically unsaturated group equivalent were evaluated by the following methods, respectively. Tables 1 and 2 show the obtained results.
[0180] (Determination of weight average molecular weight)
[0181] In the synthesis examples and comparative synthesis examples, the weight average molecular weight of the obtained polyurethane (A) is a value measured in terms of polystyrene by gel permeation chromatography (Shodex (registered trademark) GPC-101 manufactured by Showa Denko K.K., hereinafter referred to as GPC). The measurement conditions of GPC are as follows.
[0182] Column: LF-804 manufactured by Showa Denko K.K.
[0183] Column temperature: 40°C
[0184] Sample: 0.2 mass % tetrahydrofuran solution of polyurethane (A)
[0185] Flow rate: 1ml / min
[0186] Eluent: Tetrahydrofuran
[0187] Detector: RI detector (differential refractive index detector)
[0188] (Urethane bond concentration)
[0189] It is a theoretical value calculated from the amount of each raw material added.
[0190] (Ethylenically unsaturated group equivalent)
[0191] It is a theoretical value calculated from the amount of each raw material added.
[0192] (Synthesis Examples 2 to 9, Comparative Synthesis Examples 1 to 6)
[0193] Polyurethanes (A-ii) to (A-ix) and (cA-i) to (cA-vi) were obtained in the same manner as in Synthesis Example 1 except that the polyols and polyisocyanates described in Tables 1 and 2 were used in the blending amounts shown in Tables 1 and 2. The weight average molecular weight, urethane bond concentration, and ethylenically unsaturated group equivalent of each polyurethane were evaluated in the same manner as in Synthesis Example 1. The results are shown in Tables 1 and 2.
[0194] [Table 1]
[0195]
[0196] [Table 2]
[0197]
[0198] In Tables 1 and 2, "PR9000" is a compound represented by the following formula (1).
[0199]
[0200] Regarding the compounds described in Table 1 and Table 2, the following were used.
[0201] Polypropylene glycol D-2000 (Mitsui Chemicals, number average molecular weight 2000)
[0202] Polypropylene glycol D-1000 (Mitsui Chemicals, number average molecular weight 1000)
[0203] Polypropylene glycol D-400 (Mitsui Chemicals, number average molecular weight 400)
[0204] · Epoxy acrylate (manufactured by Showa Denko K.K., IPOKISHI (trademark) SP-16LDA) · PR9000: Laromer (registered trademark) PR9000 (manufactured by BASF)
[0205] ·Isophorone diisocyanate (Disophorone diisocyanate I, manufactured by Sumika Chemicals)
[0206] ・Coronet HX: Isocyanurate of 1,6-hexamethylene diisocyanate (manufactured by Tosoh)
[0207] ·Hydrogenated compound of diphenylmethane diisocyanate (Dousuemac W, manufactured by Sumika Chemicals)
[0208] ·1,6-Hexamethylene diisocyanate (manufactured by Asahi Chemical)
[0209] ·2-Hydroxyethyl acrylate (produced by Osaka Organic Chemical Industry)
[0210] (Example 1)
[0211] <Preparation of Adhesive Composition PU1>
[0212] 50 parts by mass of the polyurethane (Ai) obtained in Synthesis Example 1 as the polyurethane (A), 50 parts by mass of EHA as a monofunctional (meth)acrylate as the monomer (B) containing an ethylenically unsaturated group, 0.6 parts by mass of Irg-184 as a photopolymerization initiator (C), and 20 parts by mass of IPM as a plasticizer (D) were mixed and mixed using a disperser at 25° C. to prepare an adhesive composition PU1 involved in Example 1.
[0213] <Production 1 of protective sheet PUS1>
[0214] A protective sheet having an adhesive layer on one side of a substrate of an optical PET film is produced. First, the above-modulated adhesive composition PU1 is applied to an optical PET film (A4300 manufactured by Toyobo Co., Ltd.) with a thickness of 75 μm or a PET film (HY-S10 manufactured by Toyama Film Co., Ltd.) with a thickness of 75 μm as a substrate using an applicator. The coated adhesive composition is covered with a peeling PET film (E7006 manufactured by Toyobo Co., Ltd.) with a thickness of 75 μm. Next, an ultraviolet irradiation device (manufactured by Iglabix Co., Ltd., UV irradiation device 3 kW, high-pressure mercury lamp) is used to irradiate the sheet covered with the peeling PET film with ultraviolet rays from the side of the peeling PET film to photocure the adhesive composition and produce an adhesive layer. The irradiation distance of ultraviolet light is 25cm, the lamp moving speed is 1.0m / min, and the irradiation amount is 1000mJ / cm 2 . The thickness of the cured adhesive layer was calculated by subtracting the thickness of the optical PET film 75 μm and the thickness of the peeled PET film 75 μm from the measured value after measuring the thickness of the protective sheet using a direct-reading thickness gauge. The measuring surface of the direct-reading thickness gauge is a circular plane with a diameter of 5 mm, and the measuring force is set to 0.8 N. A protective sheet PUS1 of Example 1 with a thickness of 71 μm of the adhesive layer was obtained. The protective sheet PUS1 was evaluated for the coating surface strength (pencil hardness) of the adhesive layer, the peel strength of the protective sheet, the cut chips and the cracks of the adhesive layer by the following evaluation method. The results are shown in Table 3.
[0215] <Preparation 2 of sample PUS1 for tensile test>
[0216] A sample PUS1 for tensile test in which both sides of the adhesive layer are peelable PET films was prepared in the same manner as in Preparation 1 of the protective sheet except that a 75 μm thick peelable PET film (manufactured by Toyobo Co., Ltd., E7006) was used as the substrate. The tensile test (elongation, tensile strength) was evaluated by the following evaluation method. The results are shown in Table 3.
[0217] (Examples 2 to 21, Comparative Examples 1 to 15)
[0218] <Preparation of adhesive composition>
[0219] Adhesive compositions PUS2 to 21 and cPS1 to 15 according to Examples 2 to 21 and Comparative Examples 1 to 15 were prepared in the same manner as in Example 1 except that the components and their blending amounts described in Tables 3 to 7 were used.
[0220] <Production of protective sheet 1>
[0221] The protective sheets PUS2 to 21 and cPUS1 to 15 of Examples 2 to 21 and Comparative Examples 1 to 15 were obtained by the same method as in Example 1 except that the adhesive compositions PUS2 to 21 and cPUS1 to 15 obtained above were used. The protective sheets were evaluated for the coating surface strength (pencil hardness) of the adhesive layer and the peel strength of the protective sheet by the same evaluation method as in Example 1. The results are shown in Tables 3 to 7.
[0222] <Preparation of samples for tensile test 2>
[0223] The adhesive compositions PUS2 to 21 and cPS1 to 15 obtained above were used, and the samples PUS2 to 21 and cPUS1 to 15 for tensile tests of Examples 2 to 21 and Comparative Examples 1 to 15 were obtained by the same method as in Example 1. The samples for tensile tests were evaluated for tensile tests (elongation and tensile strength) by the same evaluation method as in Example 1. The results are shown in Tables 3 to 7.
[0224] [Table 3]
[0225]
[0226] [Table 4]
[0227]
[0228] [Table 5-1]
[0229]
[0230] [Table 5-2]
[0231]
[0232] [Table 6]
[0233]
[0234] [Table 7]
[0235]
[0236] The following compounds were used as the compounds in the table: EHA: 2-ethylhexyl acrylate (manufactured by Toagosei Co., Ltd.)
[0237] LA: Lauryl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.)
[0238] TMPTA: trimethylolpropane triacrylate (M-309, manufactured by Toagosei Co., Ltd.)
[0239] Irg-184: 1-Hydroxycyclohexyl Phenyl Ketone (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0240] IPM: エキセパールIPM (made by Kao Corporation)
[0241] HY-S10: Made by Higashiyama Fukuro Co., Ltd.
[0242] A4300: Made by Toyobo Co., Ltd.
[0243] <Coating surface strength (pencil hardness)>
[0244] The produced protective sheet was cut into a size of 100 mm × 100 mm, and the peeling PET film was peeled off. The device used an electric pencil scratch hardness tester (manufactured by Yasuda Seiki Co., Ltd., product name "No.553-M"). In addition, the pencil used was the pencil "Yuni (trade name)" of Mitsubishi Pencil Co., Ltd. Furthermore, according to JIS K 5600-5-4, under the condition of 100 g load, the pencil hardness of the adhesive layer surface of the protective sheet was measured.
[0245] <Peel strength of protective sheet>
[0246] The produced protective sheet was cut into a size of 25 mm×150 mm, and the release PET film was peeled off. Next, the exposed adhesive surface was bonded to a glass plate, and a 2 kg rubber roller (width: about 50 mm) was reciprocated once to produce a measurement sample.
[0247] 30 minutes after the pressure bonding, a tensile test was performed in a 180° direction at peeling speeds of 0.3 m / min and 2.4 m / min, and the peel strength (g / 25 mm) of the protective sheet to the glass plate was measured in accordance with JIS Z0237.
[0248] <Tensile test (elongation, tensile strength)>
[0249] The samples prepared for the tensile test are Figure 1Cut into a dumbbell shape of 5 mm in width and 50 mm in length as shown, peel off the PET films on both sides to expose the adhesive layer. The elongation at break and the breaking strength (tensile strength) were measured according to the method of JIS K 7161-1:2014. The device used a tensile testing machine (made by Stable MicroSystems). The tensile test of the adhesive layer was carried out under the conditions of a distance of 20 mm between markings and a tensile speed of 100 mm / min. The elongation was calculated according to the following formula (A).
[0250] Test piece size:
[0251] Total length: 50mm
[0252] Parallel length: 25mm
[0253] Distance between marking lines: 20mm
[0254] Parallel width: 5mm
[0255] Thickness refer to Table 3~7
[0256] Clamping width: 20mm
[0257] Distance between fixtures: 30mm
[0258] Elongation = {(distance between markings at break) - (initial distance between markings 20 mm)} / (initial distance between markings 20 mm)
[0259]
[0260] <Cut off chips and cracks in the adhesive layer>
[0261] The produced protective sheet was cut with a pinnacle blade (blade height: 0.80 mm, blade angle: 50° (manufactured by Tsukaya Blade Manufacturing Co., Ltd.)) to peel off the PET film. The upper side was made into an adhesive layer, and the lower side was made into a base layer. The end surface of the adhesive layer after cutting was observed with a microscope (magnification: 800 times (manufactured by Hilock Co., Ltd. RH-2000)), and evaluated according to the following criteria.
[0262] "Evaluation criteria for cutting chips and cracks in adhesive layer"
[0263] 1: No cutting chips or cracks were observed in the adhesive layer (e.g. Figure 2 Cross-sectional view shown)
[0264] 2: Cutting chips were observed in part of the adhesive layer, but no cracks were observed (e.g. Figure 3 Cross-sectional view shown)
[0265] 3: Cracks were observed in part of the adhesive layer, but no cutting chips were observed.
[0266] 4: Cutting chips or cracks are observed throughout the adhesive layer (e.g. Figure 4 Cross-sectional view shown)
[0267] Industrial Availability
[0268] According to the present invention, an adhesive composition can be provided that can reduce the generation of cutting scraps during cutting and the damage of the adhesive layer, and has an adhesive layer with appropriate peeling force and strength. Therefore, an adhesive layer as a cured product of the above-mentioned adhesive composition can be provided, and a protective sheet can be provided that has an adhesive layer that reduces the generation of cutting scraps during cutting and the damage of the adhesive layer, and has an adhesive layer with appropriate peeling force and strength.
Claims
1. An adhesive composition comprising: Polyurethane (A), a monomer (B) containing an ethylenically unsaturated group, and Photopolymerization initiator (C), The polyurethane (A) is a polyurethane having a skeleton including a structure derived from a polyol and a structure derived from a polyisocyanate, and having an ethylenically unsaturated group at a terminal. The weight average molecular weight of the polyurethane (A) is 3,000 to 30,000. 2 . The adhesive composition according to claim 1 , wherein the polyol is a polyoxyalkylene polyol having a number average molecular weight of 300 to 1800. 3 . The adhesive composition according to claim 1 , wherein the polyurethane (A) has an ethylenically unsaturated group equivalent of 900 to 3000 g / mol. 4 . The adhesive composition according to claim 1 , wherein the concentration of urethane bonds in the polyurethane (A) is 1.0 to 5 mol / kg. 5 . The adhesive composition according to claim 1 , wherein the polyurethane (A) has an ethylenically unsaturated group at a site other than a terminal. 6 . The adhesive composition according to claim 1 , wherein the polyisocyanate comprises a polyisocyanate containing an ethylenically unsaturated group and a polyisocyanate containing no ethylenically unsaturated group.
7. The adhesive composition according to claim 1 or 2, wherein the monomer (B) containing an ethylenically unsaturated group contains a monofunctional (meth)acrylate (B1), and the monofunctional (meth)acrylate (B1) is a chain alkyl (meth)acrylate, and the carbon number of the chain alkyl is 6 to 18. 8 . The adhesive composition according to claim 1 , wherein the ethylenically unsaturated group-containing monomer (B) comprises a monofunctional (meth)acrylate (B1) and a polyfunctional (meth)acrylate (B2).
9. The adhesive composition according to claim 8, wherein The monofunctional (meth)acrylate (B1) is contained in an amount of 5 to 89% by mass and the polyfunctional (meth)acrylate (B2) is contained in an amount of 0.1 to 30% by mass based on 100% by mass of the total of the polyurethane (A) and the ethylenically unsaturated group-containing monomer (B).
10. The adhesive composition according to claim 1 or 2, wherein The polyurethane (A) and the ethylenically unsaturated group-containing monomer (B) are contained in an amount of 10 to 90% by mass and 10 to 90% by mass, respectively, based on 100% by mass of the total of the polyurethane (A) and the ethylenically unsaturated group-containing monomer (B). The adhesive composition according to claim 1 , further comprising a plasticizer (D).
12. The adhesive composition according to claim 11, wherein The photopolymerization initiator (C) is contained in an amount of 0.05 to 5 parts by mass, and the plasticizer (D) is contained in an amount of 1 to 30 parts by mass, based on 100 parts by mass of the total of the polyurethane (A) and the ethylenically unsaturated group-containing monomer (B).
13. A cured product of the adhesive composition according to claim 1 or 11.
14. The cured product according to claim 13, wherein the elongation at break is 92 to 300%, and the breaking strength is 300 to 800 g / mm 2 . 15 . A protective sheet comprising a substrate and an adhesive layer formed on one surface of the substrate and comprising the cured product according to claim 13 .
